IMPLEMENTASI PERATURAN DAERAH NOMOR 11 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH DI KOTA BATAM - Yusup Parsoran Togatorop; Lenny Husna (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Each type of waste has a different method of management and must be appropriate to its type so as not to create problems in the community. The growing population of the land is having an impact on increasing the amount of waste generated by the community. Loss No. The 2013 Problem Formulation examines how to review the overall Waste Management Implementation System in Bottom City from 11 and what factors influence Waste Management in Bottom City that examines the theory, responsibility, and environment of waste management implementation. It is used as a practical sociological approach to the Batam City Environmental Services Office and the community with direct maintenance data collection techniques. The data collected and the information are qualitatively descriptive analyzes, i.e. it is a method of analyzing the data, collecting and selecting the data obtained from the research according to its quality and truth and then specifically evaluating it